Developmental screening of healthy children between 6-24 months - Yurumez Solmaz, Esra; Ayberk, Ulku (The European Research Journal, 2017)
Objectives. Developmental screening of healthy children from early childhood provides to identify high-risk children, early diagnose of developmental delay, better prognosis, correspond direction of family and treatment efficacy. The aim of this study was to evaluate the developmental stages for healthy children referring to the pediatric clinic for early childhood check-ups. Methods. The development of 328 children was evaluated. It is found that; awareness skills of infants with siblings were better than those without siblings. The infants attended to by caregivers had limited word usage compared with those cared for by mothers and relatives. The developmental stages were evaluated by using Social-Communication Area Screening Test for Infants (SCASI). Results. The developmental stages of infants whose mothers were graduated from university were better than the other infants in terms of awareness skills. In addition, social content skills in terms of communication levels and total points were better in infants cared for by mothers and relatives than the others, and it appears that those cared for by relatives were better compared to those only looked after by mothers. Our study indicated that according to SCASI scores, 6.1% of infants were in the risk group. Conclusions. During the first years, regular check-ups and recording of the development are very important in terms of ensuring that there is early intervention in the case of any delay in development stages. Screening tests that can be used easily, regularly repeatable, including observation of parents and having short evaluation process should be extended.